DIGITAL GAME BASED LEARNING IN SECOND LANGUAGE ACQUISITION (Web of Discoveries: Journal of Analysis and Inventions, 2024)
In the process of language acquisition, digital games are regarded as one of the essential parts to develop collaborative learning and problem-solving skills. It is generally agreed that DGBL is an effective tool to motivate learners to obtain second language by fostering the learning process and make the lessons more enjoyable. Therefore, it has pedagogical and theoretical objectives to interact with students and keep balance between educational value and fun. To be more accurately, numerous researches have been investigated innumerable effects on using digital games during academic performance. In the past decades, the area of applying digital games has increased dramatically.